2008
DOI: 10.1021/cm703314p
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Ordering and Microstructural Effects in the Ferromagnetic Perovskite La0.5Ba0.5CoO3: Impact upon Magnetotransport Properties

Abstract: The synthesis and structural study of the stoichiometric perovskite La 0.5 Ba 0.5 CoO 3 have allowed three forms to be isolated. Besides the disordered La 0.5 Ba 0.5 CoO 3 and the perfectly ordered layered LaBaCo 2 O 6 , a third form called nanoscale-ordered LaBaCo 2 O 6 , is obtained. As evidenced by transmission electron microscopy investigations, the latter consists of 112-type 90° oriented domains fitted into each other at a nanometer scale which induce large strains and consequently local atomic scale lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
90
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 26 publications
8
90
0
Order By: Relevance
“…[6][7][8] The high temperature physical properties of LBCO are rarely studied due to the structure failure of the bulk material in a reducing environment. Recently, we have fabricated epitaxial single crystalline LBCO thin films on ͑001͒ LaAlO 3 ͑LAO͒, enabling one to systematically study the electrical transport properties of LBCO under various environments.…”
mentioning
confidence: 99%
“…[6][7][8] The high temperature physical properties of LBCO are rarely studied due to the structure failure of the bulk material in a reducing environment. Recently, we have fabricated epitaxial single crystalline LBCO thin films on ͑001͒ LaAlO 3 ͑LAO͒, enabling one to systematically study the electrical transport properties of LBCO under various environments.…”
mentioning
confidence: 99%
“…8,9 Raveau's group systematically studied the fully oxidized nanoscale-ordered LaBaCo 2 O 6 , disordered La 0.5 Ba 0.5 CoO 3 , and the oxygendeficient ordered LaBaCo 2 O 5.5 and concluded that various interesting phenomena in these systems are originated from the locking of magnetic spins in the nanodomain structures. 1,2 To fully understand the physical phenomena in these complex systems, single crystalline materials are becoming critical for tackling these problems. We have fabricated single crystalline highly epitaxial ͑LaBa͒Co 2 O 5.5+␦ thin films and found that the as-grown LBCO thin films have extraordinary sensitivity to reducing-oxidizing environments and the exceedingly fast surface exchange rate at high temperature.…”
mentioning
confidence: 99%
“…However under H = 90 kOe measurement condition the resistivity is increased and these two observed -MR peaks at 15 and 235 K are suppressed to 1.4 and 1%, respectively. The -MR seen under the low temperature region seems to be explained in terms of grain boundary effects [25,[35][36][37]. For x = 0.15 sample, under H = 70 kOe condition, the +MR at room temperature (4.6%) decreases by decreasing temperature and attain -MR crossover at 205 K and at 20 K it shows -MR about 1.3%.…”
Section: Resultsmentioning
confidence: 90%